Realizing Creative Innovative Education through Increasing Digitalization Skills in Learning with Canva Media in the Era of Smart Society 5.0: Wujudkan Pendidikan Inovatif Kreatif melalui Peningkatan Kemampuan Digitalisasi dalam Pembelajaran dengan Media Canva di Era Smart Society 5.0 - S. Sama'; Syaiful Bahri; Muh. Misbahudholam AR. (Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of community service activities is based on various findings about problems owned by partners, namely SDN Kepanjin Kec. Sumenep City, Sumenep Regency. The forms of the problem are: a). Because some teachers have not utilized technology in the learning process and b). the learning process is still carried out conventionally. So that the proposing team offers solutions to provide understanding and increase the knowledge of partner teachers about the use of technology through Canva media. This community service activity at SDN Kepanjin was held in March 2022. The activities carried out included workshops for teachers of SDN Kepanjin. The steps of this service activity include; preparation of activities, implementation of activities, and post-activities. The conclusions of the results of community service are; a). Community service activities about realizing creative innovative education through increasing digitalization capabilities in learning with canva media in the era of smart society 5.0 have been carried out well. b). Community service activities at SDN Kepanjin received an enthusiastic response from the teachers. and c) Workshop participants understand well how to use canva media in the learning process. Abstrak Tujuan dari dilaksanakan kegiatan pengabdian kepada masyarakat berdasarkan dari berbagai temuan tentang permasalahan yang dimiliki oleh mitra yaitu SDN Kepanjin Kec. Kota Sumenep Kab.sumenep. Adapun bentuk masalah yaitu: a). Karena beberapa guru belum memanfaatkan tekhnologi dalam proses pembelajaran dan b). proses pembelajaran masih dilakukan secara konvensional. Sehingga tim pengusul menawarkan solusi untuk memberikan pemahaman dan meningkatkan pengetahuan guru mitra tentang penggunaan teknologi melalui media Canva. Kegiatan pengabdian masyarakat di SDN Kepanjin ini dilaksanakan pada bulan Maret 2022. Kegiatan yang dilaksanakan meliputi workshop untuk guru-guru SDN Kepanjin. Adapun langkah-langkah kegiatan pengabdian ini meliputi; persiapan kegiatan, pelaksanaan kegiatan, dan pasca kegiatan. Kesimpulan dari hasil kegatan pengabdian kepada masyarakat yaitu; a). kegiatan pengabdian kepada masyarakat tentang mewujudkan pendidikan inovatif kreatif melalui peningkatan kemampuan digitalisasi dalam pembelajaran dengan media canva di era smart society 5.0 telah terlaksana dengan baik. b). Kegiatan pengabdian kepada masyarakat di SDN Kepanjin mendapatkan respon yang antusias dari para guru. dan c) Peserta workshop memahami dengan baik tentang cara penggunaan media canva dalam proses pembelajaran.